Agroactive Compounds of Microbial Origin - Tanaka, Y.; Omura, S.
Microbial metabolites attract increasing attention as potential pesticides. They are expected to overcome the resistance and pollution that have accompanied the use of synthetic pesticides. Several microbial metabolites, such as avermectin have proved useful as agroactive agents. In this review, we attempt to identify newer agroactive microbial metabolites with feasible activity or interesting action sites from those reported in recent years. In addition, microbial and chemical modifications of existing microbial agrochemicals are discussed to illustrate the usefulness of these technologies in potentiating agroactivity and stability. We discuss the possibility of future discovery of excellent microbial agrochemicals, and the importance of effortsto promote positive public perception and public acceptance of pesticide chemicals.